Factors influencing the selection of environmental inpact services in South Africa - Simpson, Ainsley (University of the Witwatersrand, Johannesburg, 2008)
The environmental consulting industry in South Africa is still in a growth phase, and the dominant service offering is that of Environmental Impact Assessments (EIA). Understanding consumer behaviour in the purchase process of environmental services will enable service providers to effectively target and service their desired markets. This research examined factors influencing the selection of EIA Consultants in South Africa, specifically in the pre-purchase phase. This included determining the nature of the service offering and the related perceptions of risk as well as the information sources consulted and criteria used as risk reducing strategies. The research was conducted by means of a structured written survey, which was completed by 77 respondents across South Africa. The research revealed that EIA’s are experience offerings, that is, they are easy to assess after the service has been rendered. It was also determined that the major factor contributing to the selection process is the multi-faceted nature of the service, as this can lead to negative reputation-based consequences. One such facet of EIA’s is the length of time required to complete the process. Temporal risk was found to be the most dominant concern, followed by financial risk, specifically the incurrence of unforeseen costs. It was established that consumers consult personal non-marketer controlled information sources as a method of reducing risk; most notably, consultants known to the developers through previous experience. Reliability, represented largely by tangible criteria, and reputation, comprising less tangible criteria, were found to be the factors underlying the evaluation of environmental consultancies. The research highlighted the need for EIA Consultants to understand the buying behaviour of their target market to effectively understand and manage perceived risks. Tangible indicators of reliability and reputation that address these risk areas must be a central theme in any direct marketing strategies developed. Furthermore, continuous improvement of processes and systems is essential such that a healthy reputation, based on sound experience, can be developed and maintained well into the future.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Business Administration, to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2025
Keywords: Environmental impact services; South Africa; SDG-13: Climate action; SDG-12: Responsible consumption and production